Character Formation Habituation in P5 as Co-Curricular Based Learning in Surakarta City Schools - Yunazar, Rizky; Liestyasari, Siany Indria (Jurnal Dimensi Pendidikan dan Pembelajaran, 2025)
One of the educational transformations in the current era is emphasized on the formation of student character. Internalization of character in students can be formed through the P5 program. The P5 program is an initiative designed to integrate Pancasila values into project-based student character education. In character development, character formation habits are needed which include habitus, capital, arena, and practice. The aims of this research is to examine the habituation of student character formation through the P5 program theme in educational units. Qualitative method with a case study-based approach is used in this research. Data collection techniques in this study used interviews, observations, and document analysis. This study was conducted at three school levels with the aim of comparing the implementation patterns of character formation in the P5 program on students at SD Negeri Joglo No. 76 Surakarta, SMP Negeri 1 Surakarta, and SMA Batik 1 Surakarta. The Miles, Huberman, and Saldana models, namely data reduction, data presentation, and drawing conclusions is used to analyse data. The data findings in this study indicate differences in the implementation process of the P5 program at three levels of schools in Surakarta City and that habituation is needed in internalizing the six dimensions of the Pancasila student profile based on the P5 project.